2005
DOI: 10.1094/phyto-95-1072
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control Efficiency of Fusarium Wilt of Tomato by Nonpathogenic Fusarium oxysporum Fo-B2 in Different Environments

Abstract: Efficiency of nonpathogenic Fusarium oxysporum Fo-B2 for the biological control of Fusarium wilt of tomato, caused by F. oxysporum f. sp. lycopersici CU1, was examined in different environments: a growth chamber with sterile soil-less medium, a greenhouse with fumigated or nonfumigated soil, and nonfumigated field plots. Inoculation of Fo-B2 onto tomato roots significantly reduced the severity of disease, but the efficiency of disease suppression decreased as the experimental environment became less controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 15 publications
2
24
0
1
Order By: Relevance
“…Root colonization by EU0013_90S increased depending on the EU0013_90S spore concentration. Shishido et al (2005) have reported differences in efficiency of nonpathogenic Fusarium oxysporum in the biocontrol of tomato wilt under different environmental conditions. They reported that a biocontrol agent was more effective when used in sterile seedbeds, compared with non-sterile soil, as it decreased competition from indigenous soil microbes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Root colonization by EU0013_90S increased depending on the EU0013_90S spore concentration. Shishido et al (2005) have reported differences in efficiency of nonpathogenic Fusarium oxysporum in the biocontrol of tomato wilt under different environmental conditions. They reported that a biocontrol agent was more effective when used in sterile seedbeds, compared with non-sterile soil, as it decreased competition from indigenous soil microbes.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies using Penicillium oxalicum and non-pathogenic F. oxysporum (e.g. Duijff et al 1998;Larena et al 2003;Shishido et al 2005), have demonstrated significant reductions in the incidence and severity of tomato Fusarium wilt disease. Plant growth promoting fungi (PGPF) have also been reported to suppress plant diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Both fungi are apparently well-adapted to forest nursery environments. Previous studies using crops other than Douglas-fir in nurseries have shown that non-pathogenic F. oxysporum can prevent disease by pathogenic F. oxysporum (Fuchs et al, 1999;Fravel and Larkin, 2002;HuertasGonzalez et al, 1999;Larkin and Fravel, 2002;Shishido et al, 2005). We therefore hypothesized that some nonpathogenic isolates of F. oxysporum may have the potential to protect conifer seedlings from virulent isolates of F. commune.…”
mentioning
confidence: 94%
“…Antagonism implies direct interaction between two microorganisms that share the same ecological niche. Such antagonists can compete with pathogens for nutrients, diminish pathogens by parasitism, inhibit growth of pathogens through antibiosis or even induce systemic resistance in plants (Shishido et al, 2005). Earlier studies demonstrated that the volatile and non-volatile compounds of a variety of fungal microorganisms inhibit the activity of pathogenic fungi.…”
Section: Introductionmentioning
confidence: 99%